PERLINDUNGAN HUKUM BAGI PEMEGANG PERTAMA MEREK LOKAL JOLLIBEE TERHADAP MEREK TERKENAL ASING - Karin , Cika Zulyani; Bustani, Simona (Tribuere, 2024)
Brands are included in intellectual property rights where the rights holder of the brand is given legal protection for both local and foreign brands. The issues raised are how was the protection of Jollibee brand holder in Indonesia according to Law Number 20 of 2016 concerning Brands and Geographical Indications, and how was the Commercial Court Judge's decision in deciding the Jollibee brand dispute based on Law Number 20 of 2016 concerning Brands and Geographical Indications. This research is conducted by normative legal research with a descriptive nature, the data used is secondary data obtained through literature studies, then the data is analyzed by qualitative with drawing conclusions deductively. The results of the study showed that Legal Protection for the holder of the Jollibee Brand Owned by Karsino is given due to Brand Certification he has, however, for the first registered trademark can be cancelled if it violates the provisions of Article 21 Paragraph (3). The judge's decision in case Number 9/PDT.SUS-MEREK/2023/PN.NIAGA.JKT.PST that rejected the application to cancel the Jollibee trademark owned by Karsino is not in accordance with Article 21 paragraph (3) of the Trademarks and Geographical Indications Law.